顎下腺造影検査により診断に至った顎下腺粘液嚢胞の1例 - 小宮, 正道; 相澤, 聡一; 真宮, 淳; 吉田, 美昭; 絹川, 雅夫; 北野, 尚孝 (日本口腔外科学会雑誌, 2017)
Mucocele generally occurs in salivary glands, but very rare arises in submandibular glands. Moreover, the diagnosis of submandibular gland mucocele is complicated because of the similarity between submandibular gland mucoceles and plunging ranulas. In this report, we describe a case of submandibular gland mucocele. An 11-year-old girl who had a painless swelling in the right submandibular region was referred to our department. Magnetic resonance imaging showed a lesion extending from the right submandibular space to the sublingual space. The lesion emitted high signal intensity on T2-weighted images. We found leakage of contrast media around the lower side of the right submandibular gland on sialography of the submandibular gland. We therefore diagnosed a mucocele arising in the submandibular gland. The cystic lesion and submandibular gland were completely excised. There have been no signs of recurrence or disease complications as of 60 months after surgery.